2018
DOI: 10.1017/s0022149x18000299
|View full text |Cite
|
Sign up to set email alerts
|

Do behavioural defence mechanisms explain different levels of trematode infections in congeneric hosts?

Abstract: Susceptibility and tolerance to parasite infection vary greatly between host species. The congeneric isopod species Austridotea annectens and Austridotea lacustris often occur in sympatry and can both serve as intermediate hosts for the trematode Maritrema poulini. However, the intensity and prevalence of infections vary greatly in natural populations, with A. annectens often being heavily infected and A. lacustris rarely being infected. To shed light on the factors that may be involved in infection avoidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Zohar and Holmes, 1998; Bollache et al ., 2001), and may play a role in reduced pairing by P. fluviatilis . However, as A. lacustris is a very rare host (<1%; Goellner et al ., 2018), the difference in pairing success in this species may be due to indirect effects of infected competitors. Past studies have suggested that M. poulini in A. annectens affects the distribution of A. lacustris , and mediates the competition between these species (Friesen et al ., 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Zohar and Holmes, 1998; Bollache et al ., 2001), and may play a role in reduced pairing by P. fluviatilis . However, as A. lacustris is a very rare host (<1%; Goellner et al ., 2018), the difference in pairing success in this species may be due to indirect effects of infected competitors. Past studies have suggested that M. poulini in A. annectens affects the distribution of A. lacustris , and mediates the competition between these species (Friesen et al ., 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The isopod, A. annectens is also commonly infected by M. poulini . Maritrema poulini is also found in A. lacustris but at extremely low prevalence (Presswell et al 2014, Friesen et al 2018, 2020, Goellner et al 2018). As both M. poulini and C. parvum can successfully complete transmission between first and second intermediate hosts in a mesocosm setting and parasite exposure rate can be controlled, these trematodes were selected as focal parasites and used to create continuous exposure (infective larval stages of both species present in the mesocosm through infected first intermediate host snail) and arrested exposure (no additional exposure to infective parasite larval stages of either species in mesocosm) treatments.…”
Section: Methodsmentioning
confidence: 99%